(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
New taxa of bryophytes Syntrichia ruralis (Hedw.) F.Weber & Mohr (Pottiaceae) and Riccia rhenana Lorbeer (Ricciaceae) are described. In the former, the new var. polysporogonica Boiko is characterized by having 1–6 sporogones per stem. In the latter, the var. violacea Boiko is distinguished by blue-violet leaves and violet amphigastria.